Pediatric Acute External Laryngeal Trauma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Larynx and adjacent anatomical structures have complicated physiological functions and mechanical features. Traffic accidents, penetrating stab wounds and shot wounds, sports matches, and occupational accidents cause external laryngeal trauma. In the management of laryngeal trauma, maintenance of airway patency has priority. In this case report, we will mention of a 15-year-old male patient with a blunt laryngeal trauma and also the approach to laryngeal traumas.
Keywords: Pediatric laryngeal trauma; penetrating trauma; airway management